NEED ANALYSIS OF DIGITAL TEACHING MATERIALS WITH STEM APPROACH AND FLIP BOOK-FORMED TO IMPROVE SELF-REGULATED SKILLS FOR PRE-SERVICE TEACHERS - Apit Fathurohman; Lintang Auliya Kurdiati; Syarifudin Syarifudin; Esti Susiloningsih; Rani Mega Putri (SPEKTRA: Jurnal Kajian Pendidikan Sains, 2024)
Technology-integrated teaching resources are a valuable tool for enhancing the teaching and learning process. Students attain less than optimal learning objectives and master competencies when innovative approaches to using technology-integrated instructional materials are not taken. In order to improve the self-regulated learning skills of students in pre-service teacher professional education programs, this research aims to identify the need for opportunities to develop interactive digital teaching materials with a STEM approach in New Technology in Teaching and Learning courses that are integrated with flip book-formed technology. A qualitative design was employed in the conduct of this study. A requirements analysis questionnaire is used in conjunction with interviews as part of the data collection method. The study's findings demonstrate that students in pre-service teachers' professional education programs typically read lecturer-provided reference books and use instructional materials from the Ministry of Education. The study's findings also demonstrate that students' opinions about the possibility of creating and using flip books to support the use of interactive digital teaching resources with a STEM approach are favorable. It is intended that the findings of this study will serve as a foundation for future research as it relates to creating and utilizing flip book-formed STEM interactive digital teaching materials to support pre-service teachers' professional development.